Rainhas Apis mellifera africanizadas tolerantes à inseticida neonicotinoide - Pizzaia, William Cristian da Silva (2016)
The interaction between bees and plants assured vegetables success in cross-pollination, increasing the vigor of the species, and increasing the production of fruits and seeds. Bees are the main pollinators of flowering plants and crops and one of the main reasons for the disappearance of the agricultural areas of bees is excessive or incorrect use of insecticides. However agriculture is heavily dependent on the use of pesticides used in order to deter pests of various crops. The use of pesticides affects pollinating insects like bees Apis mellifera. Colony Collapse Disorder associated with insecticides has caused damage to life of bees. This research aimed to select queen bees A. mellifera africanized tolerant to neonicotinoid Thiamethoxam, produced four generations of bees kept in chronic contamination to that insecticide and perform tests to validate tolerance. Bioassays were mounted in an apiary in Iguatemi Experimental Farm where bees were subjected to a contact with neonicotinoid insecticide on filter paper. Selection of queens was carried out maintaining the parental generations to F4 which were subjected to 24 hour toxicity test in B.O.D. and critical electrolyte concentration (C.E.C.) for evaluation of tolerance to the insecticide neonicotinoid. The results showed that bees have become tolerant to neonicotinoid insecticide Thiamethoxam after four generations of selection kept in sublethal concentrations of insecticide.